Managing CSR initiatives from the Islamic perspective: the case of Bank Islam Malaysia Berhad (BIMB) - Fathiyyah Abu Bakar,; Mohd ‘Atef Md Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2016)
From the Islamic perspective, corporate social responsibility (CSR) is a mean to maintain a good relationship with Allah (SWT), other human beings and the environment. However, the process of managing CSR initiatives in accordance with Islamic principles has been given scarce attention in the literature. Thus, this study aims to describe and develop a managerial guideline for the process of managing CSR initiatives based on the Tawhid and Shariah paradigms. Using the case study approach, CSR key players and beneficiaries at Bank Islam Malaysia Berhad were interviewed, several series of in-field observations of these events were conducted and the CSR documentation was reviewed to better understand the processes involved. The findings of this study indicate that the processes of managing CSR initiatives at Bank Islam have become more systematic and well-planned. Hence, the proposed managerial guideline may add new insights to the CSR body of knowledge and may help business entities to manage CSR more systematically.